Banking Panics and the Lender of Last Resort in a Monetary Economy - Makoto Watanabe; Tarishi Matsuoka (Tinbergen Institute, 2019)
This paper studies the role of a lender of last resort (LLR) in a monetary model where a shortage of bank's monetary reserves (or a banking panic) occurs endogenously. We show that while a discount window policy introduced by the LLR is welfare improving, it reduces the banks' ex ante incentive to hold reserves, which increases the probability of a panic, and causes moral hazard in asset investments. We also examine the combined effect of other related policies such as a penalty in lending rate, liquidity requirements, and constructive ambiguity.
Keywords: E40; 330; Monetary Equilibrium; Banking Panic; Moral Hazard; Lender of Last Resort